Performance analysis of the fabricated animal feed mixer machine - Ardian, Aan; Wikantara, Astana Aji; Aditya, Zaky Ahmad; Kusdiyarto, Prihatno (Faculty of Engineering, Universitas Negeri Yogyakarta, 2024)
This research focused on the development of an animal feed mixer machine to improve mixing capacity. The research used an experimental model and involved need analysis, design, development, implementation, and evaluation. The goal was to determine the optimal rotational speed of a stirrer screw for different types of animal feeds as well as understand the stages of making the machine and its working principle. The process involved manufacturing the frame, shaft, transmission, screw fins, sheet metal process, and assembly. The results shows that the animal feed mixer machine with a stirring speed of 312.3 rotations/minute was able to produce 958.3 kg of feed in one hour. This stirring speed provides the best fuel consumption, which is 676.5 ml/hour. The mixer has a safe element on the reduction shaft, with 115.8 kg.mm of torque and 5.82 kW of power. Thus, this mixer is an efficient and productive solution for the animal feed industry.